2006
DOI: 10.1007/s10164-006-0019-7
|View full text |Cite
|
Sign up to set email alerts
|

Aggression and dominance in matched groups of subadult Icelandic horses (Equus caballus)

Abstract: We studied sex differences in the nature of aggression and dominance behaviour in two newly formed groups of 1-year-old Icelandic horses. One herd contained nine geldings, the other nine mares. The groups were matched with regard to dominancedetermining traits such as age, weaning age, composition of native herd, social experience, genetic origin, body condition and maternal dominance status. Highranking individuals of both sexes were more aggressive, high-ranking males were older, and high-ranking females had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 54 publications
3
25
0
Order By: Relevance
“…These findings are consistent with the sex differences observed in 1-year-old Icelandic horses by Vervaecke et al (2007), and suggest that males contest dominance relationships more frequently than females. Males may contest dominance relationships more often than females because benefits of high rank are higher for polygynous males than for females (Trivers 1972;Vervaecke et al 2007). Dominance relationships among males were also less stable, as changes occurred after the two breeding stallions returned to the group.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These findings are consistent with the sex differences observed in 1-year-old Icelandic horses by Vervaecke et al (2007), and suggest that males contest dominance relationships more frequently than females. Males may contest dominance relationships more often than females because benefits of high rank are higher for polygynous males than for females (Trivers 1972;Vervaecke et al 2007). Dominance relationships among males were also less stable, as changes occurred after the two breeding stallions returned to the group.…”
Section: Discussionsupporting
confidence: 90%
“…The frequency of agonistic interactions given per individual in this study is within the range reported for bachelor groups of Przewalski horses (Feh 1988: 0.76 h -1 ;Christensen et al 2002: 1.46 h -1 ) and domestic horses (Christensen et al 2002: 0.63 h -1 ). Consistent with the findings of other studies on horse bachelor groups (Feh 1988;Christensen et al 2002;Vervaecke et al 2007), breeding groups (e.g. Houpt and Keiper 1982;Keiper and Sambraus 1986;Keiper and Receveur 1992;Heitor et al 2006) and feral stallions in multi-male bands (Miller 1981), intensity of agonistic interactions was low, consisting mostly of threats.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Dominance hierarchies are found in primates [10,11], social carnivores [12,13], ungulates [14,15], birds [16][17][18][19], fish [20], and even crustaceans [21,22] and insects [23]. These group-level social structures form and stabilize on the basis of perceptions and actions necessarily made at the individual level [24].…”
Section: Introductionmentioning
confidence: 99%